JBoss AS 7 Development. - Marchioni, Francesco (Packt Publishing, 2013)
This book will kick-start your productivity and help you to master JBoss AS development. The author's experience with JBoss enables him to share insights on JBoss AS development in a clear and friendly way. By the end of the book, you will have the confidence to apply all the newest programming techniques to your JBoss applications. If you are a Java architect or developer who wants to get the most out of the latest release of the JBoss application server, then this book is for you. You are not expected to have accumulated experience on the application server though you must know the basic conc.